Una nota sobre un procedimiento bayesiano para meta-análisis con datos binarios con alta presencia de ceros - Miguel A. Negrín; María Martel; Francisco J. Vázquez-Polo (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2015)
– The propose of this paper is to develop a Bayesian procedure that adequately account for studies with zero observations in meta-analysis and then we focus the problem in the context of the Bayesian selection models. Also, attention is focused to the link distribution between effectiveness in each study/center and the meta-effectiveness. We present an objective Bayesian method where all quantities of interest jointly with a Bayesian test for equality between treatments are also obtained. A couple of examples with are developed in depth using the pro- posed Bayesian meta-analysis for the binomial model. Basically, we obtain a Bayesian model for meta-analysis for sparse binomial data without considering transformations and/or corrections in variable/parameters. In respect to the examples considered, we do not find a relevant difference between treatments.
Keywords: C11; C49; 330; Bayesian analysis; Farlie-Gumbel-Morgenstern link; meta-analysis